1997
DOI: 10.1146/annurev.psych.48.1.299
|View full text |Cite
|
Sign up to set email alerts
|

Personnel Selection

Abstract: This chapter reviews literature from approximately mid-1993 through early 1996 in the areas of performance and criteria, validity, statistical and equal opportunity issues, selection for work groups, person-organization fit, applicant reactions to selection procedures, and research on predictors, including ability, personality, assessment centers, interviews, and biodata. The review revolves around three themes: (a) attention toward criteria and models of performance, (b) interest in personality measures as pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
97
1
8

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 148 publications
(109 citation statements)
references
References 156 publications
3
97
1
8
Order By: Relevance
“…Assertiveness, a facet of Extraversion suggesting firm leadership, also was more likely than Extraversion (as a broad trait) to yield meaningful and generalizable relationships with quality of teaching. These two outcomes involving FFM facets are consistent with the view that the facets are more likely than the five broader factors to be predictive of performance outcomes (Borman et al,1997;Hough, 2003;Hough & Schneider, 1996, Murphy, 1996Paunonen, 1998;Paunonen & Ashton, 2001). Indeed, a number of writers have emphasized the heuristic value of a multilevel hierarchical approach to personality (Carroll, 2002;Coan, 1964;Costa & McCrae, 1995;Digman, 1997;Emmerich, 1968;Hough & Schneider, 1996;John, 1990;John & Srivastava, 1999;Saucier & Goldberg, 2003).…”
Section: Five-factor Modelsupporting
confidence: 72%
See 2 more Smart Citations
“…Assertiveness, a facet of Extraversion suggesting firm leadership, also was more likely than Extraversion (as a broad trait) to yield meaningful and generalizable relationships with quality of teaching. These two outcomes involving FFM facets are consistent with the view that the facets are more likely than the five broader factors to be predictive of performance outcomes (Borman et al,1997;Hough, 2003;Hough & Schneider, 1996, Murphy, 1996Paunonen, 1998;Paunonen & Ashton, 2001). Indeed, a number of writers have emphasized the heuristic value of a multilevel hierarchical approach to personality (Carroll, 2002;Coan, 1964;Costa & McCrae, 1995;Digman, 1997;Emmerich, 1968;Hough & Schneider, 1996;John, 1990;John & Srivastava, 1999;Saucier & Goldberg, 2003).…”
Section: Five-factor Modelsupporting
confidence: 72%
“…This study bears a resemblance to attempts to identify trait complexes or constellations (Ackerman, 1999;Ackerman, Bowen, Beier, & Kanfer, 2001;Ackerman & Heggestad, 1997;Borman et al, 1997;Lubinski, 2000;Lubinski & Benbow, 2000;Prediger, 1999;Reeve & Hakel, 2000;Snow, Corno, & Jackson, 1996). Unlike research on trait constellations, however, this study did not include measures of abilities and knowledge that were separate from the NBPTS assessments themselves.…”
Section: Possible Implications For Constellation Theoriesmentioning
confidence: 72%
See 1 more Smart Citation
“…9 Research has shown that "The Big Five" personality traits (extraversion, agreeableness, openness, conscientiousness, and neuroticism; see Borman, Hanson, andHedge, 1997, andMorgeson et al, 2007), are useful guidelines for the selection of Antarctic staff. Personality is thought to predict contextual performance rather than task performance (Borman et al, 1997). An integral part of this is disposition or motivation, which is attributed to personality (Borman et al, 1997 a limited number of co-workers, applicants need to have a high degree of social competency, i.e.…”
Section: Mental Fitnessmentioning
confidence: 99%
“…Personality is thought to predict contextual performance rather than task performance (Borman et al, 1997). An integral part of this is disposition or motivation, which is attributed to personality (Borman et al, 1997 a limited number of co-workers, applicants need to have a high degree of social competency, i.e. the skill to interpret other people's behaviour and mood adequately and interact appropriately (Steel, 2015).…”
Section: Mental Fitnessmentioning
confidence: 99%